Effectiveness of Self-Instructional Module on Knowledge regarding Maternal Deprivation Syndrome among Mothers in Selected Community Areas - Divya Dongari; Komala Sesha Kumar; Dongari Maadhavi (Journal of Applied Nursing and Health, 2022)
Background: Life is an incredible gift God gives to human beings, but the first day of everybody’s life will start in the mother's womb. The importance of mothers in life can neither be defined nor can it be measured. The present study attempted to evaluate the effectiveness of a self-instructional module on knowledge regarding maternal deprivation syndrome among mothers in the selected community areas of Bangalore. Methods: A pre-experimental one-group pretest-posttest design was commenced on 50 mothers with children below five years using non-probability convenient sampling, and knowledge was assessed using a structured knowledge questionnaire. The study's findings showed that the self-instructional module was adequate Results: Results of research shows that out of 50 mothers, 34 had inadequate, ten had moderate knowledge, and 6 had adequate knowledge before giving the self-instructional module. After the self-instructional module's administration, none had inadequate knowledge, 16 (32%) had moderate knowledge, and 34 (68%) had adequate knowledge. Therefore, knowledge of the mothers was improved post-test. The ‘t’ value was 16.50, greater than the table value of 1.677 at 0.05 significant, and was found to be highly significant Conclusion: No significant association was found between post-test knowledge score and selected socio-demographic variables except family income.